Studies at the school by the sea eaudiobook - Colgan, Jenny (School by the Sea, 2024)
The long-awaited and never-before published finale in New York Times bestselling author Jenny Colgan's delightful School by the Sea series. After all those lessons, it's time to graduate.... Beloved literature teacher Maggie Adair loves her life at the prestigious Downey House boarding school on the gloriously sunny, windy English coast. It was there that she found her footing as a teacher and fell in love with her colleague David—the two great anchors of her life. But these days Maggie's feeling restless, lured by the promise of a different life back in her Scottish hometown. How can you follow your heart when it seems to be taking you in two directions at once? Meanwhile, Maggie's favorite students are abuzz at the thought of graduation and set to fly the nest to their next adventure. What will life hold for mercurial Fliss, glamorous Alice, and shy, hard-working Simone when they finally finish their studies at the school by the sea? Will Maggie stay to welcome the next class of girls, or will she too graduate to new adventures?